(untitled) (Semiárida, 2020)
Nine areas with short grasslands were analyzed in the central and Southeastern region of the Province of La Pampa to determine the standing crop at the end of the growing period Piptochaetium napostaense and Stipa tenuis, two cool desirable species, were dominant in all these areas. Only few warm species were present Aerial phytomass ranged between 200 to 350 gDM/m2.